2023
DOI: 10.1002/mar.21862
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot or human? The impact of online customer service on consumers' purchase intentions

Abstract: Artificial intelligence (AI) chatbots and human employees have emerged as the dominant forms of online customer service. However, existing research rarely connects the service differences between them in terms of product type, ignoring the interactivity between the two. This study reveals the effect of matching customer service type (AI chatbot vs. human) to product type (search vs. experience) on consumers' purchase intentions through four experiments, revealing the psychological mechanism and boundary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…First, the study establishes that the purchase intention of a potential customer is encouraged by a satisfactory customer experience with chatbot usage. These results are consistent with previous studies which found that experience can be positively correlated with consumers' behavioral intentions, namely purchase intention (Bilal et al, 2024;Chen et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…First, the study establishes that the purchase intention of a potential customer is encouraged by a satisfactory customer experience with chatbot usage. These results are consistent with previous studies which found that experience can be positively correlated with consumers' behavioral intentions, namely purchase intention (Bilal et al, 2024;Chen et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The significance of AI chatbots in customer service and retention (Chen et al, 2021;S. Chen et al, 2023) also finds a counterpart in our study, where freelancers reported improved client satisfaction through AI-enhanced workflows.…”
Section: Discussionsupporting
confidence: 72%
“…Freelancers in our study cited efficiency and productivity gains as primary motivators for adopting AI chatbots, echoing findings by Abdallah et al (2023), who highlighted customer acceptance of AI chatbots in the banking sector, emphasizing efficiency in service delivery (Abdallah et al, 2023). Similarly, Chen, Le, and Florence (2021) and underscored AI chatbots' role in enhancing online customer experiences, aligning with freelancers' appreciation for AI in streamlining workflows and improving output quality (Chen et al, 2021;S. Chen et al, 2023).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Adding a different dimension to the discourse, Chen et al embarked on a journey to enhance the explanatory power of machine learning models in understanding consumer purchase behavior in search advertising [39]. They introduced a random forest model that factored in anchoring effects, which can sometimes bias rational consumer behavior.…”
Section: Consumer Behavior Clustermentioning
confidence: 99%